PERAN KOPERASI UNIT DESA DALAM MENINGKATKAN KESEJAHTERAAN PETANI DI KABUPATEN JEMBRANA - Putra, I Kadek Beriko; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 9 (2023): Vol.12.No.9.SEPTEMBER. 2023[586-649]DO - 10.24843/EEP.2023.v12.i09.p01, 2023)
The problems experienced by rural community farmers encourage farmers to have the desire that Village Unit Cooperatives can be formed as credit distribution to carry out their business activities. Overcoming problems at the farmer level can be done through farmer institutions, one of which is cooperatives. The purpose of this study was to analyze the effect of cooperative income, the number of active cooperative members' participation, and the amount of cooperative members' savings simultaneously and partially on the welfare of farmers in Jembrana District. This study uses a quantitative approach and is associative. The research location is in Jembrana Regency, while the objects in this study are cooperative income, the number of active cooperative members' participation, the amount of savings of cooperative members, and the welfare of farmers. The data analysis technique used to solve the problems in this study is a multiple linear regression analysis technique. The results showed that cooperative income, participation of active cooperative members, and savings of cooperative members had a significant effect simultaneously and partially had a positive and significant effect on the welfare of farmers in Jembrana District.  Keywords: cooperative income, participation of active cooperative members, savings of cooperative members, welfare of farmers